2021
DOI: 10.1186/s12947-020-00235-w
|View full text |Cite|
|
Sign up to set email alerts
|

Usefulness of speckle tracking echocardiography and biomarkers for detecting acute cellular rejection after heart transplantation

Abstract: Background Acute cellular rejection (ACR) is a major complication after heart transplantation. Endomyocardial biopsy (EMB) remains the gold standard for its diagnosis, but it has concerning complications. We evaluated the usefulness of speckle tracking echocardiography (STE) and biomarkers for detecting ACR after heart transplantation. Methods We prospectively studied 60 transplant patients with normal left and right ventricular systolic function w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 44 publications
3
16
1
1
Order By: Relevance
“…Our data contrast with earlier work showing decreased LVGLS and RV-FWLS in a population with more than 6 months of HT ( 7 ) or a smaller population with a lower rejection frequency with less than 1 year of HT ( 6 ). However, Tseng et al ( 9 ) observed similar results for LVGLS in a retrospective study that included patients with less than 1 year of HT without considering the period of time between transplant and EMB of less than or more than 6 months.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our data contrast with earlier work showing decreased LVGLS and RV-FWLS in a population with more than 6 months of HT ( 7 ) or a smaller population with a lower rejection frequency with less than 1 year of HT ( 6 ). However, Tseng et al ( 9 ) observed similar results for LVGLS in a retrospective study that included patients with less than 1 year of HT without considering the period of time between transplant and EMB of less than or more than 6 months.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study by Mingo-Santos et al ( 6 ) suggested that global LV and RV free wall longitudinal strain (FWLS) could help rule out significant ACR during the first year after HT. Other studies found similar results for GLS ( 7 9 ). Combined with biomarkers, Cruz et al ( 7 ) reported that patients with ACR had significantly lower values of LVGLS, RV-FWLS, and LV-Twist and higher levels of troponin I than patients without significant ACR.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations